Oman Construction Industry Prospective on Cause of Construction Material Waste - Alias Imran Latif , Qadir Bux (International Journal of Integrated Engineering, 2020)
Construction industry is second largest industry in gulf countries, that continuously rapidly growing. Similar to other countries around the world, construction industries in gulf region also facing problems due to oil industry uncertainties. Construction industry of gulf countries, construction material waste is getting higher concern. This paper aims to identify various factors in construction management causing construction material waste at Muscat, and Nizwa cities in Oman. Seventy-one (71) factors were collected from literature around the world and organized in structured questionnaire distributed amongst the construction experts focusing clients, consultants and contractors involved in the construction projects. The questionnaire was designed in such a way to collect construction waste causing factors in five major categories in (Design, Handling, Workers, Management, Procurement, and Site conditions). The collected data were analyzed by using Average Index method for each factor. Furthermore, construction material waste causing factors analyzed by individual response of client, consultant and contractor prospective. Analysis identified that ‘frequent design changes’; ‘wrong material storage’; ‘worker’s mistakes during construction’; ‘poor supervision’; ‘mistakes in quantity surveys’; and ‘poor site conditions’; are highest significant causes in each category respectively. The result of this study is useful to create or/and improve guideline considering waste generated from construction industry, to avoid problems in looming construction. It is concluded that the government organizations or/and construction industry itself can develop or improve legislation for avoiding construction material waste.